Conselho Municipal de Educação na gestão educacional do município de São Luís-MA: destaques para a atuação dos/das conselheiros/as - GOMES, Brenda Cristina Ferreira (2021)
This work had as research object the Municipal Council of Education (CME) of São Luís – MA and the educational management of that municipality. The main objective was to analyze the performance of the CME in educational management, having as reference the normative bases of this body and the performance of the counselors. Therefore, we sought to identify the purposes and attributions of the CME according to the legal documents; characterize the constituent elements in the normative legal basis of the São Luís CME; analyze the role of counselors in the educational management of the municipality and unveil the challenges and possibilities in the role of the CME in the educational management process in São Luís. From the survey of a state of knowledge, carried out on the CAPES platform, which included the productions published about the CMEs in the period 2014 to 2017. A bibliographical review was also carried out with studies by authors such as Freitas (2004); Montaño and Duriguetto (2011); Cavalcanti (2016); Zander and Tavares (2016) on the political transformations of the 1990s within the scope of State Reform and the resignifications in the concepts of autonomy and participation linked by decentralization processes. Cury (2000; 2006), Bordignon (2009), Souza (2010) and Lima (2014), among others, supported the understanding of Education Councils, their purposes, functionalities and legal attributions based on the understanding of their nature as a well-founded body on the principles of social control and democratic management. Documentary research was used to analyze the normative legal basis of the CME, which comprises the Law creating the CME (Law No. 6.617/2019), the Internal Regulation of 2014 and the minutes of the plenary sessions held in the period 2017 to 2019. In order to add data to the work and seeking an approximation with the counselors and the space of the São Luís CME, field research was carried out through two visits to the CME and, given the circumstances of the coronavirus pandemic, it was carried out. whether the application of an online questionnaire as a data collection instrument, prepared on the Google Forms platform. The analysis of the research data was carried out from the content analysis as suggested by Bardin (1977) through the use of context units and enumeration rules through the presence (or absence), frequency and co-occurrence of indicators in the documents. The research results showed that the role of the CME in the educational management of the municipality of São Luís still lacks, mainly, stimuli with regard to mobilizing action, since its activity is mostly centered on technical-administrative activities that are important and fundamental, however, they must be exercised in equanimity with the actions of a political-formative character of society so as not to lose sight of the political-social nature of the CME. For this reason, the counselors have operated mainly as administrative technicians, frequently acting in the regularization and organization of school institutions in the municipal education network, since, according to the analyzed minutes, these are the processes that most demand the role of counselors.